The Fifth Queen Crowned - Ford, Ford Madox, 1873-1939 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Fifth Queen Crowned" by Ford Madox Ford is a historical novel published in 1908. It is the final book in a trilogy that presents a highly fictionalized account of Katharine Howard's time at Henry VIII's court. The series follows the impoverished young Catholic noblewoman as she navigates the dangerous intrigues of Tudor England, gradually rising to become the king's fifth wife. Ford reimagines Katharine as devout and learned rather than flighty, creating an impressionistic portrait of power, faith, and fate in a treacherous world of spies and schemers. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Fifth_Queen
Release date is 2008-12-07
E-text prepared by Verity White, Suzanne Shell, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Catharine Howard, Queen, consort of Henry VIII, King of England, -1542 -- Fiction